DESENVOLVIMENTO, CARACTERIZAÇÃO E AVALIAÇÃO DE NANOEMULSÃO CONTENDO ANFOTERICINA B - Campos, Daniele de (2021)
In recent decades, invasive fungal infections (IFI) have shown a significant increase, especially due to the higher incidence of cases linked to co-infection associated with other pathologies, where species of the genus Candida represent one of the most common causes of IFI in humans. Among the antifungals approved for the treatment of IFIs, amphotericin B (AmB) stands out, as it is of a broad spectrum. However, its clinical use has been limited due to its side effects, the most serious of specially nephrotoxicity. In addition, AmB has low solubility, permeability in biological membranes and stability in the gastric environment, which makes it impossible to be administered orally. Thus, the objective of this work was to develop a nanoemulsion based on oleic acid for carrying AnB, in order to expand its physical-chemical and biological characteristics. The nanoemulsion (NM) is composed of an oil phase (oleic acid and polysorbate 80) and an aqueous phase (water and lecithin), being obtained by the high shear homogenization method. Parameters such as: type and concentration of the surfactante and proportion of oil phase: aqueous phase were optimized. NM was characterized in terms of mean diameter, polydispersity index, zeta potential, morphology, in vitro release (gastrointestinal fluids and physiological pH), stability and antifungal activity. The nanoemulsion containing amphotericin B (NM-AmB), had an average diameter of 250,0±15,0nm, a polydispersion index of 0,180±0,020 and a zeta potential of -27,3±1,5mV. The kinetic profile of AmB released from NM-AmB was characterized according to the Higuchi model. The release in the gastrointestinal fluids demonstrated that NM-AmB presents stability in the simulated gastric fluid obtaining percentages of AmB release of 11,2% (pH 1,2). In the simulated intestinal fluid, AmB presented a release rate corresponding to 52,0% (pH 6,8) in 6 hours, demonstrating that the basic pH increases the release of AmB contained in NM. The total percentage of release in PBS buffer during the 96 hours of the experiment was 14,5%, which suggests stability in this type of receptor medium. In addition, NM-AmB showed high antifungal action against studied strains (C. albicans 0546 VITROIDSTM, C. albicans clinic, C. glabrata clinic, C. tropicalis clinic and C. Krusei). Therefore, based on the results obtained, it can be said that the nanoemulsion formulation containing Amphotericin B is a promising candidate as a carrier system for AmB.